Estudo e caracterização em filmes de perovskita e salofeno para aplicação em células solares - Silva, Francisco Nascimento (2023)
Schiff base introduction (salophene) has been researched to improve the stability of perovskite solar cells based on methylammonium lead iodide (MAPbI3). Salophene was chosen as an additive to the antisolvent solution to minimize the degradation process under ambient conditions. Perovskite (MAPbI3) was deposited on transparent conductive fluorinedoped tin oxide (FTO) substrates. We show that it is possible to improve the stability of MAPbI3 by properly incorporating salophene molecules into the perovskite matrix. The films were characterized by ultraviolet-visible absorption (UVvis), photoluminescence (PL), excitation photoluminescence (PLE) and X-ray diffraction (XRD) spectroscopy, to determine the stability of their optical and structural properties. We carried out a study of the electrical characteristics, current versus voltage, stability, and reproducibility of the devices with MAPbI3/salophene as the active layer, produced at the Laboratory of Nanotechnology and Solar Energy (LNES). When exposed to light, the original layer of perovskite MAPbI3 is transformed into PbI2, which can also be evidenced by the decrease in UV-vis absorption and XRD patterns of the material. Through (XRD), we verified that the MAPbI3/salophene perovskite presents better structural stability under adverse humidity and lighting conditions. The introduction of salophene in the perovskite matrix alters the degradation process, delaying the appearance of yellowish regions, characteristic of PbI2 in films. The film containing (salophene) was stable in relation to the film without salophene, after 700 hours, exposed in an atmosphere with 50 - 60% relative humidity, indicating that the introduction in the active layer, provided greater stability to the perovskite film. Thus, the perovskite MAPbI3/salophene shows optical properties and stability for application in devices such as perovskite solar cells.